Prevalens av subkliniskt smittade katter med vingelsjuka i Göteborg jämfört med Uppsala - Eriksson, Jonas (2005)
Borna disease virus (BDV) is a virus with capability to cause neurological disease in several species of mammals and of ostriches. Also humans are suspected to be susceptible to the virus, as the viral RNA and antibodies against BDV have been found in some humans with psychiatric diseases, like schizophrenia and depression. In Sweden there is a disease called staggering disease in cats, associated to BDV-infection. This disease often has a fatal progress. Definite diagnosis is reached by histo-pathological and immunohistochemical examination of the central nervous system. In these cats, a nonsuppurative meningoencephalomyelitis is induced by the virus. The disease gives rise to signs like ataxia of the hind limbs, changes in behavior, inability to withdraw the claws, mostly in the hind limbs and to pain from the lumbosacral spine. In Sweden, apart from cats there have also been reported Borna-infection in horses and lynx. The way of infection is not clearly understood, but there are theories that rodents and some birds may work as naturally reservoirs of BDV. In Sweden there is evidence that staggering disease in cats occurs in the region of Mälardalen. There is however no larger studies made for the rest of Sweden. Blood samples were collected in Gothenburg and Uppsala to study the prevalence of antibodies against BDV in healthy, outdoor cats that were more than one year of age. Realtime-PCR and ELISA-studies were performed. More studies are needed to make the diagnostics to work and to be able to study the prevalence of BDV in cats outside the region of Mälardalen.